FDI, Aid, Terrorism: Conditional Threshold Evidence from Developing Countries - Simplice Asongu; Uchenna Efobi; Ibukun Beecroft (African Governance and Development Institute (AGDI), 2015)
We investigate how foreign aid dampens the effects of terrorism on FDI using interactive quantile regressions. The empirical evidence is based on 78 developing countries for the period 1984-2008. Bilateral and multilateral aid variables are used, while terrorism dynamics entail: domestic, unclear, transnational and total number of terrorist attacks. The following findings are established. First, while the effects of multilateral aid are consistently significant with positive threshold evidence, bilateral aid is only positively significant in bottom quantiles. Second, with the slight exception of transnational terrorism in bilateral aid regressions, the impacts of terrorism dynamics are unexpectedly positive, in: (i) bottoms quantiles with domestic terrorism and the 0.25th quantile with total terrorism, for bilateral aid regressions, and (ii) the 0.25th quantile with domestic terrorism and bottom quantiles of transnational terrorism, for multilateral aid regressions. Third, interactions between terrorism and foreign aid dynamics unexpectedly yield negative effects in: (i) bilateral aid and domestic terrorism in bottom quantiles and (ii) multilateral aid and domestic (transnational) terrorism in the 0.25th(bottom) quantile(s). The modifying threshold value of bilateral aid is higher than that of multilateral aid. Fourth, there is positive threshold evidence from GDP growth, infrastructural development and trade openness. Policy implications are discussed.
Additional information: This is a working paper. Authors welcome suggestions and comments.
Keywords: C52; D74; F23; F35; O40; 330; FDI; Foreign aid; Terrorism; Quantile regression